Immobilization of strontium-loaded zeolite A by metakaolin based-geopolymer. Issue 5 (1st April 2017) - Xu, Zhonghui; Jiang, Zao; Wu, Dandan; Peng, Xi; Xu, Yahong; Li, Na; Qi, Yijin; Li, Ping
Abstract: Zeolites are the preferred inorganic ion exchange materials for purifying radioactive waste liquid. Radionuclide-loaded zeolites, which are considered to be radioactive waste, are strictly required to be encapsulated within a solid matrix. In this paper, we investigate the feasibility of immobilizing exhausted zeolite A, loaded with 90 Sr radionuclide, in metakaolin based-geopolymer. The geopolymer solidification blocks had better mechanical performance and leaching resistance in deionized water, sulfuric acid, magnesium sulfuric and acetic acid buffer solutions than the cemented blocks. While the compressive strength of the geopolymer solidification product was 37.62 MPa after curing for 28 days, the equivalent value for the cement block was only 11.32 MPa. The geopolymer solidification blocks also exhibited even lower compressive strength loss after high-temperature and freeze-thaw cycles tests. XRD and EDS analysis indicated that most of the strontium radionuclide in the geopolymer solidification blocks was incorporated in the zeolite structure as the charge balancing cation. The microscopic analysis revealed that geopolymer matrix appeared more compact and dense, and encapsulated the Sr-loaded zeolite A more tightly than did the cement. Therefore, it could be concluded that metakaolin based-geopolymer are more compatible with exhausted zeolite A and present a remarkable advantage for radioactive waste immobilization.